Digitalizing Disaster Evacuation Management: A Responsive Public Service Model for Vulnerable Groups in Local Government - Erfan Wahyudi; Lalu Ahmad Murdhani (Yayasan Hisnul Muslim Lombok, 2025)
This study examines the digitalization of disaster evacuation management as a responsive public service model for vulnerable groups at the local government level. The study is based on the argument that evacuation management should not be understood merely as an emergency logistical operation, but also as an inclusive public service system that determines how affected populations are identified, protected, served, monitored, and referred during disasters. Using a qualitative case study approach, this research analyzes institutional readiness, data management practices, inter-agency coordination, shelter services, and the protection of vulnerable groups, including older persons, persons with disabilities, women, children, pregnant women, and people with chronic illness. Data were collected through in-depth interviews, field observations, and document analysis involving local disaster management agencies, social affairs offices, health offices, civil registration offices, communication and informatics offices, village governments, shelter managers, volunteers, and representatives of vulnerable groups. The findings show that conventional evacuation management remains constrained by fragmented data, manual registration, weak vulnerability profiling, and limited service integration. This study proposes an inclusive digital evacuation service model consisting of six components: pre-disaster vulnerability database, digital evacuee registration, vulnerability-based service classification, shelter and logistics monitoring, inter-agency referral system, and inclusive complaint handling. The novelty of this study lies in integrating disaster evacuation management, digital data governance, responsive public service, and social inclusion into a single local government framework. The proposed model enables local governments to provide evacuation services that are more accurate, accessible, accountable, and responsive to vulnerable groups.